Influence of microorganisms on uranium release from mining-impacted lake sediments under various oxygenation conditions. Issue 10 (9th September 2022) - Seder-Colomina, Marina; Mangeret, Arnaud; Bauda, Pascale; Brest, Jessica; Stetten, Lucie; Merrot, Pauline; Julien, Anthony; Diez, Olivier; Barker, Evelyne; Billoir, Elise; Poupin, Pascal; Thouvenot, Antoine; et al.
Abstract : Microbial processes can be involved in the remobilization of uranium (U) from reduced sediments under O2 reoxidation events such as water table fluctuations. Abstract : Microbial processes can be involved in the remobilization of uranium (U) from reduced sediments under O2 reoxidation events such as water table fluctuations. Such reactions could be typically encountered after U-bearing sediment dredging operations. Solid U(iv ) species may thus reoxidize into U(vi ) that can be released in pore waters in the form of aqueous complexes with organic and inorganic ligands. Non-uraninite U(iv ) species may be especially sensitive to reoxidation and remobilization processes. Nevertheless, little is known regarding the effect of microbially mediated processes on the behaviour of U under these conditions.